2016
DOI: 10.1161/hypertensionaha.116.07731
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Network Enhances the Sympathoinhibitory Component of Baroreflex of Rats Submitted to Chronic Intermittent Hypoxia

Abstract: C hronic intermittent hypoxia (CIH) is characterized by frequent activation of the peripheral chemoreceptors, which over time produces several cardiovascular dysfunctions, including mild hypertension. [1][2][3][4] The CIH-induced hypertension in rats can be prevented by sympathetic nerve chemical denervation, renal sympathectomy, and adrenal medullectomy. 1,5,6 Rats submitted to CIH also presented a larger fall in arterial pressure in response to ganglionic blockade and augmented power of oscillatory component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(64 reference statements)
1
10
0
1
Order By: Relevance
“…RVLM neurons exhibit different patterns of activity entrained by the respiratory pattern generator, with peaks of activity modulated by either I or PI 19 , 22 , 36 38 . We showed that Alst inhibited TH-positive inspiratory-modulated, but not TH-negative post-inspiratory-modulated RVLM bulbo-spinal barosensitive pre-sympathetic neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RVLM neurons exhibit different patterns of activity entrained by the respiratory pattern generator, with peaks of activity modulated by either I or PI 19 , 22 , 36 38 . We showed that Alst inhibited TH-positive inspiratory-modulated, but not TH-negative post-inspiratory-modulated RVLM bulbo-spinal barosensitive pre-sympathetic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…RVLM C1 and non-C1 neurons are both modulated by respiration 19 and both show increased respiratory-related activity during hypoxia or hypercapnia 20 , 21 . In this regard, our previous studies have demonstrated that rats submitted to chronic intermittent hypoxia (CIH) exhibit active expiration 10 and an increase in the firing frequency of expiratory-modulated pre-sympathetic RVLM C1 neurons 19 , 22 , which was also reflected in sympathetic post-ganglionic activity 10 . Indeed, we proposed that this expiratory-related sympathetic activity may contribute to the sustained hypertension induced by CIH in rats 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The correct placement of the guide cannula was confirmed at the end of the experiment by injection of Evans Blue (2% in 10 μl; Sigma-Aldrich, St. Louis, USA) and its visible presence in the intracerebroventricular system. After electrophysiological experiments, LC neurons were filled with biocytin using the previously described juxtacellular labelling method (200 ms pulses of 1.0–4.0 nA at 2.5 Hz for 1–3 min) 70 . All signals were acquired by a data acquisition system (5 KHz; CED 1401; Cambridge Electronic Design, UK) controlled by a computer running Spike 2 software (Cambridge Electronic Design).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic intermittent hypoxia (CIH) is an experimental model of repetitive peripheral chemoreceptor activation (Braga, Soriano, & Machado, ; Fletcher, ; Fletcher et al., ; Moraes et al., ; Prabhakar, Peng, Jacono, Kumar, & Dick, ; Zoccal, Bonagamba, Oliveira, Antunes‐Rodrigues, & Machado, , Zoccal, Bonagamba, Paton, & Machado, ). Long‐term exposure to intermittent hypoxia has been shown to lead to sustained hypertension in male and female rats (Fletcher et al., ; Moraes et al., ; Perim, Bonagamba, & Machado, ; Souza, Bonagamba, Amorim, Moraes, & Machado, , ; Souza, Amorim, Moraes, & Machado, ; Zoccal, Bonagamba, Antunes‐Rodrigues, & Machado, , Zoccal et al., 2007b, , ).…”
Section: Introductionmentioning
confidence: 99%